Konjunkturanalyse for Bornholm, 1987 til 1996. Kapitel 3: arbejdsmarkedet pa Bornholm 1987 til 1996 - Lars Lund (Copenhagen Business School (CBS), Department of Economics, 2001)
– Using the seminal work of Blanchard and Katz on regional development as a frame a small number of macro economic key figures are looked upon for Bornholm, the Capital Area and the country. The model used is presented and even though the analysed time period is short, a comparison is made with the hypotheses or predictions of the model regarding employment, rate of unemployment and wages or wage incomes. Participation rates and migrations are also touched upon. An expectation that a negative chock to employment on Bornholm in 1988 permanently reduced the level of employment has not been confirmed; rather it seems that negative trends are found for Bornholm and for Københavns Amt. The data do not show a return to equilibrium values of relative wages and rates of unemployment after a business cycle.
hdl:10398/7580
Keywords: E10; E20; E24; 330; macro economic; regional development; Bornholm; Denmark; employment; unemployment